Factors Affecting Supply Chain Management in Moroccan Manufacturing Firms - Guoping, Cheng; Hanane, Karroumi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
The goal of this research is to test the main factors which affect the chain management in Moroccan manufacturing firms through concentrate on morocco Distilleries firms. furthermore, this research aimed to set supply chain management used by morocco Distilleries firms, define the effectiveness of supply chain management practices at morocco Distilleries firms and determine factors affecting supply chain management at morocco Distilleries firms. The result find that the Supply chain management in Moroccan industrial firms was effectively practiced. The constructs ranked high or identified to be frequently used in supply chain practiced were: planning for supply chain, supplier(s) relationship management, manufacturing flow management, product development management, customer service management, order fulfilment, and audit performance of supply chain. Moreover, the study find that the supply chain management in Moroccan industrial firms was very effective and well performing. All seven studied instruments for measuring effectiveness of the said management. The instruments were selection of supplier(s), purchasing, transporting, manufacturing, stocking, warehousing and distribution. These were positive and significant at the 5% level of significance.